Monitoring and control of biofilm in the Extractive Membrane Bioreactor (EMBR) - Ng, Josephine Su Hua (2016)
The accumulation and development of biofilm in Extractive Membrane Bioreactor (EMBR) poses difficulties in the process for wastewater treatments. Monitoring and control of biofilm in EMBR is a crucial element to provide better efficiency and effectiveness for the treatments. A generic biofilm growth model was explored, which consists of 5 main stages, from initial adhesion to a surface to the final release of surface cells for further colonization. Extracellular Polymeric Substances (EPS), namely protein, polysaccharides and DNA, each has important roles in various stages of biofilm development and structural support. As mature biofilm has a relatively stable protective structure, by deducing the trend in production of EPS by bacterial cells in the early stages, further experiments could be explored to deter the growth of biofilm. In this experiment, colorimetric experiments using spectrophotometer were conducted over 4 day intervals on sludge and 3 pure bacterial strains, namely Pseudomonas aeruginosa (PAO1), Escherichia coli K-12 (MG1655), Pseudomonas putida (KT2440), to determine the concentration of individual EPS. This report will provide an overview of biofilm development, a summary on the basic functions of EPS in the growth cycle, the methods of colorimetric analysis using spectrophotometer, discussions on the results and trends obtained, and possible future plans to enhance the trends obtained.